IR spectra of paracetamol - Habiba, U; Alam, A; Rahman, S; Shamim, SUD; Piya, AA (Bangladesh Journal of Scientific and Industrial Research, 2021)
Paracetamol is a very popular medication used to treat pain and fever. IR spectra of paracetamol have been measured for powder crystals. Ab initio calculations of its equilibrium geometry and vibrational spectra were carried out for spectrum interpretation. Differences between the experimental IR spectra of crystalline samples have been analyzed. Variations of molecular structure from the isolated state to molecular crystal were estimated based on the difference between the optimized molecular parameters of free molecules and the experimental bond lengths and angles evaluated for the crystal forms of the title compounds. The role of hydrogen bonds in the structure of molecular crystals of paracetamol is investigated. Bangladesh J. Sci. Ind. Res.56(4), 255-262, 2021